2021
DOI: 10.1021/acs.analchem.1c01550
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction of Vertically Arrayed MoS2 Nanosheet/N-Doped Reduced Graphene Oxide Enabling a Nanozyme for Sensitive Biomolecule Monitoring

Abstract: Enzymes are still indispensable for bio-assaying methods in biomolecule detection by far. The unsatisfied long-term instability, high cost, and susceptibility to the physical environment of natural enzymes are obvious weak points. Here, we developed peroxidase-like heterostructured nanozyme, vertically arraying molybdenum disulfide nanosheets on a substrate layer of nitrogen-doped reduced graphene oxide (MoS2/N-rGO), with a well-pleasing stability that is characterized by the retained enzymatic activity and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Both theoretical and experimental studies have suggested that the defects created by molybdenum and sulfur in MoS 2 have enhanced the sensitivity and detection efficiency. 144 The one-pot synthesis method has been explored by Wang et could act as catalytic active sites. 145 Further, to enhance the activity of graphene the mesoporous Fe 3 O 4 has been incorporated and a 3D structure has been designed by Qiu et al for the detection of p-nitrophenol as it is an industrial effluent.…”
Section: -D Nano-carbon Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both theoretical and experimental studies have suggested that the defects created by molybdenum and sulfur in MoS 2 have enhanced the sensitivity and detection efficiency. 144 The one-pot synthesis method has been explored by Wang et could act as catalytic active sites. 145 Further, to enhance the activity of graphene the mesoporous Fe 3 O 4 has been incorporated and a 3D structure has been designed by Qiu et al for the detection of p-nitrophenol as it is an industrial effluent.…”
Section: -D Nano-carbon Nanozymesmentioning
confidence: 99%
“…Both theoretical and experimental studies have suggested that the defects created by molybdenum and sulfur in MoS 2 have enhanced the sensitivity and detection efficiency. 144 The one-pot synthesis method has been explored by Wang et al for the synthesis of 3D graphene nanocomposites of Fe 3 O 4 . The 3D structure leads to the generation of channels and voids, which could act as catalytic active sites.…”
Section: -D Nano-carbon Nanozymesmentioning
confidence: 99%
“…As glucose and oxygen react enzymatically to create H 2 O 2 , nanozymes with peroxidase activity can then be applied to indirectly determine glucose levels [69] . Such as MoS 2 nanosheets/N‐atom‐doped graphene oxide, [70] Fe 3 O 4 /MW carbon nanotubes (CNTs), [71] etc., whereas SAzymes as more active nanozymes have also been investigated for application in more sensitive assays of glucose. Min Chen group [14] designed a single iron site nanozymes (Fe‐SSN) by a sacrificial carrier approach, where the porous structure of nitrogen‐doped carbon allows for a more dispersed but guaranteed number of iron sites to achieve higher peroxidase activity.…”
Section: Biosensing Detectionmentioning
confidence: 99%
“…MOFs are the ideal carriers for drug delivery because they can easily be modified with specific molecules and exhibit low toxicity, a large surface area, and nanoenzyme (or nanozyme)‐like properties (Cai et al, 2019; Ding et al, 2020; Sun et al, 2020). Nanozymes are a class of enzyme mimics that display both the unique properties of nanomaterials and the catalytic functions of enzymes (Cao et al, 2020; Duan et al, 2020; Fang et al, 2020; Gao et al, 2007; Wang, Chang, et al, 2020; Wang, Li, et al, 2021; Wang, Wang, et al, 2019; Wei et al, 2021; Zhou, Ouyang, et al, 2021; Zhou, You, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%